A New PWM Technique With Single Phase Switched-Capacitor High-Gain Multilevel Inverter for Photovoltaic Applications - Oorappan G. Murugan; Sivaraman Pandarinathan; S. A. Lakshmanan; C. Dhanamjayulu; S. M. Muyeen (IEEE Access)
The modulation strategies employed in the Single-Phase Switched-Capacitor Multilevel (SC MLI) Inverter must produce waveform of superior quality while minimizing losses from switching. Offering an appealing substitute, Flat Pulse Width Modulation (FPWM) technique provide reduced device switching frequencies compared to traditional continuous PWM approaches. This feature generates more voltage and helps to reduce the switching losses in the converter. The paper introduces proposed FPWM techniques alongside a novel structure for a SC MLI. The proposed topology demonstrates its advantages over cutting-edge MLIs through a comparative evaluation encompassing component count, voltage stress, gain factor and cost function considerations. Moreover, experimental results confirm the efficacy of the MLI across diverse scenarios, linear and nonlinear loads, as well as dynamic testing conditions for harnessing Photovoltaic (PV) power. Furthermore, the article introduces a harmonic minimization technique for FPWM methods by adjusting the sinusoidal modulating reference to restrict harmonic amplitude while maintaining the same effective switching frequency, thereby reducing switching losses.